International commercial arbitration - Born, Gary, 1955- (Wolters Kluwer, 2021)
International Commercial Arbitration' is an authoritative 4,250 page treatise, in three volumes, providing the most comprehensive commentary and analysis, on all aspects of the international commercial arbitration process that is available.00The Third Edition of has been comprehensively revised, expanded and updated, 0- To include all legislative, judicial and arbitral authorities, and other materials in the field of international arbitration prior to June 2020. 0- It also includes expanded treatment of annulment, recognition of awards, counsel ethics, arbitrator independence and impartiality and applicable law. 0- The revised text contains references to more than 20,000 cases, awards and other authorities and will enhance the treatise?s position as the world?s leading work on international arbitration.0.